Interlayer-expanded MoS2 hybrid nanospheres with superior zinc storage behavior. (October 2021) - Jia, Hao; Qiu, Minghui; Tawiah, Benjamin; Liu, Hongqi; Fu, Shaohai
Abstract: As a promising cathode candidate, molybdenum disulfide (MoS2 ) has attracted extensive attention due to its excellent layered structure for Zn ion storage. However, the poor specific capacity and the relatively short cycling lifespan remain a challenge to fulfilling its potential applications. Herein, we successfully synthesized a highly stable MoS2 –O nanosphere with intercalated Mo–O bonds adjacent to the MoS2 layers as cathode material for Zn ion batteries (ZIBs). The results demonstrate that the degree of sulfidation contributed to the expansion of the interlayer spacing of MoS2 while the intercalated Mo–O bonds aided the structural integrity and the stability of the fabricated cathode during the repeated Zn insertion/extraction process. Due to the optimized structure, the specific capacity and cycling stability of ZIBs with MoS2 –O nanosphere cathode improved significantly over 300 cycling with an initial specific capacity of 206.7 mAh·g −1  at 100 mA g −1 . This work provides a promising approach to effectively enhance the capacity retention performance of MoS2 for ZIBs. Highlights: The MoS2 nanospheres with intercalated Mo–O bonds are used as Zn ion battery cathodes. The intercalated Mo–O bonds aided the structural integrity of the fabricated cathode. The MoS2 –O nanosphere cathode led to a high capacity of 206.7 mAh·g −1  at 100 mA g −1 . Incorporated Mo–O bonds helps improve the cycling stability and Coulombic efficiency.